The Effect Of Beginners Teacher Induction Program (PIGP) On Pedagogic Competency And Professional Competency Of Beginners Teacher - Umi Nahdiyah; Achmad Supriyanto; Ahmad Yusuf Sobri (Abjadia, 2022)
Teachers are professional educators that have a role in the development of education. so that is why important for a teacher to improve their competence. The purpose of this research is to determine the effect of the novice teacher induction program (PIGP) on the pedagogic competence and professional competence of novice teachers. Data collection was done by simple random sampling by distributing google forms. The data is processed using SmartPLS 3.0 software. The results of the analysis show that the acquisition of R square is 0.739 for pedagogic competence, while the acquisition of R square for professional competence is 74.9. The conclusion in this study is that PIGP has a positive and significant effect on the pedagogic competence and professional competence of novice teachers.